Assessment Factors of Indoor Comfort and Health in Hospital Buildings Based on Green Building Systems in Palu City - William Arrang Sarungallo; Tutang M. Kamaludin; Lilianti Y. Sunuh; Zet Mallisa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to evaluate the comfort and health levels of rooms in Anutapura Hospital, Undata Hospital, and Tadulako University Hospital, with a focus on the application of green building principles, particularly in terms of room comfort and health. The study also identifies factors influencing comfort and health, such as smoking bans, control of carbon dioxide (CO?) and carbon monoxide (CO) levels, and the use of refrigerants. The research method used is qualitative, involving interviews and field observations to gain an in-depth understanding from respondents directly involved in the hospital building construction. The respondents consisted of five people: two from Anutapura Hospital, one from Undata Hospital, and two from Tadulako University Hospital. Observations were made on facilities such as smoking prohibition signs, ventilation, air conditioning systems, and parking areas. The results show that Tadulako University Hospital scored the highest (13 points), followed by Undata Hospital (11 points), and Anutapura Hospital (8 points), based on comfort and health parameters. Tadulako University Hospital excelled in air quality control and the use of refrigerants with low Global Warming Potential (GWP). Key factors influencing room comfort and health include freedom from tobacco smoke, ventilation, CO? and CO sensors, and the use of environmentally friendly refrigerants.